ChemInform Abstract: Aloeverasides A and B: Two Bioactive C‐Glucosyl Chromones from Aloe vera Resin. Issue 52 (6th December 2016) - Rehman, Najeeb Ur; Hussain, Hidayat; Khiat, Mohammed; Al‐Riyami, Samia Ahmed; Csuk, Rene; Khan, Husain Yar; Abbas, Ghulam; Al‐Thani, Ghanim Salim; Green, Ivan R.; Al‐Harrasi, Ahmed
Abstract: The title compounds (I) display good urease enzyme inhibition activities, significant growth inhibition of the breast cancer cell line MDA‐MB‐231 as well as good antioxidant activities.